Transforming Traditional Labs into Virtual Computing Labs for Distance Education - Gercek, Gokhan; Saleem, Naveed (International Journal of Online and Biomedical Engineering (iJOE), 2008)
Abstract—The demand for on-line courses continues to rise in academia because (1) on-line courses remove time barriers that would otherwise restrict a student from pursuing academic endeavors, (2) they remove the distance barriers for academia in reaching potential students and (3) they can to some extent alleviate budgetary and physical constraints on the academia in imparting education to students. The on-line instruction mode rather easily accommodates courses in some disciplines such as history, sociology, and political science. However, it posits significant adoption challenges for courses that require hands-on computing experimentation such as computer networking, system administration, web application development and database administration. Nevertheless, given the demand for on-line courses, there is a need to devise strategies that would allow students to conduct computing experiments through remote access. This paper presents an approach to transform traditional computer labs into a virtual lab environment. Such transformation allows students to remotely conduct experiments that involve software and hardware interaction. The methodology presented here can be applied to a large number of computing courses encountered in Management Information Systems and Computer Sciences disciplines.